Saving Energy Using the Modified Heuristic Algorithm for Energy Saving (MHAES) in Software-Defined Networks - Agg, Péter András; Johanyák, Zsolt Csaba (Sensors (Basel, Switzerland), 2023)
Energy consumption is a significant concern in daily life, often neglected in terms of cost and environmental impact. Since IT networks play an essential role in our daily routines, energy-saving in this area is crucial. However, the implementation of energy efficiency solutions in this field have to ensure that the network performance is minimally affected. Traditional networks encounter difficulties in achieving this goal. Software-Defined Networks (SDN), which have gained popularity in the past decade, offer easy-to-use opportunities to increase energy efficiency. Features like central controllability and quick programmability can help to reduce energy consumption. In this article, a new algorithm named the Modified Heuristic Algorithm for Energy Saving (MHAES) is presented, which was compared to eight commonly used methods in different topologies for energy efficiency. The results indicate that by maintaining an appropriate load balance, one can save more energy than in case of using some other well-known procedures by applying a threshold value based on forecast, keeping only a minimal number of nodes in an active state, and ensuring that nodes not participating in packet transmission remain in sleep mode.